(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the association between orthostatic hypotension and postural dizziness, and determined the factors most likely related to orthostatic hypotension in patients with diabetes. Study Design: Comparative study. Place and Duration of Study: This study was conducted at the Hamdard University Hospital, Karachi between October 2010 and September 2012. Materials and Methods: The subjects were 102 consecutive non–insulin-dependent patients with diabetes and 204 age- and sex-matched control subjects. Orthostatic hypotension was defined as a decline of 20 mm Hg or more in systolic blood pressure 1 minute after standing. Postural dizziness was any feelings of dizziness, light-headedness, or faintness that occurred while standing during the examination. Results: The prevalence of orthostatic hypotension and postural dizziness in patients with diabetes was higher than in control subjects. Those patients with both diabetes and orthostatic hypotension were older and had higher supine systolic blood pressures and higher plasma glycosylated hemoglobin and fasting glucose levels. They had higher prevalence of postural dizziness, hypertension, and cerebrovascular disease, and lower standing systolic blood pressures than those without orthostaticl hypotension. They also were more often being treated with antihypertensive agents. Only 30.8% of patients with diabetes with orthostatic hypotension suffered from postural dizziness. Postural dizziness, hypertension, cerebrovascular disease, and plasma glycosylated hemoglobin levels were independently associated with orthostaticl hypotension in patients with diabetes. Conclusion: Postural dizziness, glycemic control, hypertension, and cerebrovascular disease were important determinants of orthostatic hypotension in patients with diabetes. Orthostaticl hypotension was associated with postural dizziness, but it cannot be determined clinically just from the presence of postural dizziness because the sensitivity for diagnosis of orthostatic hypotension is low.